An Assessment of the Level of Awareness of Climate Change and Variability among Rural Farmers in Taraba State, Nigeria - Oruonye, E. D (International Journal of Sustainable Agricultural Research, 2014)
Previous studies on climate change in Taraba State concentrated on the evidence of climate change in the state, awareness of climate change among students of tertiary institutions in the state and farmers perception and adaptation to climate change in northern Taraba. There is need to have a state wide research that examines climate change awareness and perception among rural farmers in Taraba State. This will greatly reduce the failures in measures to develop a state wide effective monitoring, adaptation and mitigation measures to climate change in the study state. Questionnaires were used to solicit for information from the famers in twelve LGAs of the state. The question ranges from the farmers knowledge of climate change, and how this has affected them over the years. The farmers were asked what they think about the trend of rainfall variables such as total rainfall, onset, cessation, length of rainy season and changes in temperature in the last 10 – 20 years in their area. The farmers were also asked what they think about the trend of incidence of flooding and dry spell in their areas and how this has affected them. Despite the farmers’ awareness and adaptation to climate change in the state, lack of information and capital hinders them from getting the necessary resources and technologies that facilitate adapting to climate change.